Antiretroviral therapy and mortality in rural South Africa: a comparison of causal modeling approaches - Oldenburg, Catherine; Seage, George R.; Tanser, Frank; De Gruttola, Victor; Mayer, Kenneth H.; Mimiaga, Matthew J.; Bor, Jacob; Bärnighausen, Till (American journal of epidemiology, 2018)
Abstract. Estimation of causal effects from observational data is a primary goal of epidemiology. The use of multiple methods with different assumptions relati
Advance access publication: March 23, 2018
Gesehen am 24.03.2020